85 Vasoplegia causes high cardiac energy demand and induces cardiac phosphocreatine depletion: modelling how 'the engine runs out of fuel'. (17th July 2020) - Watson, William; Green, Peregrine; Chamley, Rebecca; Burrage, Matthew; Lewis, Andrew; Neubauer, Stefan; Rider, Oliver
Abstract : Introduction: The healthy heart is at its most efficient when preload is adequate while energy requirements escalate when ionotropy or heart rate are increased. We hypothesized that in vasoplegia, loss of preload (owing to dilation of capacitance veins) and compensatory rises in heart rate and contractility would compromise the efficiency of the heart. We speculated that this may be one factor impairing cardiac function in conditions of distributive shock such as sepsis and looked to model the effects. We used cardiac magnetic resonance imaging to capture changes in cardiac volumes and contractility and magnetic resonance spectroscopy to investigate changes in ATP metabolism within the myocardium. Methods: We recruited 8 healthy volunteers (mean age 41 years, range 28-62 years; mean BMI 22.7, range 18.5-24.5) and measured their baseline cardiac volumes and function, PCr/ATP ratio and Creatine Kinase first order rate constant (CKkf), using cardiac magnetic resonance imaging and magnetic resonance spectroscopy at 3 Tesla. At the same visit, they received a glyceryl trinitrate (GTN) infusion to induce vasoplegia and the measurements were repeated. We targeted GTN infusion rate to a fall in mean arterial pressure of 15mmHg. Results: See table 1 . The GTN infusion brought about a fall in mean arterial pressure and a fall in LV end diastolic volume (indicating a reduction in preload) with expected compensatory rises in heart rate and ejection fraction. Cardiac output remained unchanged. Cardiac work (calculated as stroke volume x MAP x heart rate) fell. There was a fall in PCr/ATP ratio on GTN, while flux through creatine kinase (indicating rate of generation of ATP from Phosphocreatine) rose and the first order rate constant of the creatine kinase enzyme (CKkf, the rate limiting step in this process) rose by over 50%. Conclusions: The rise in CKkf and CK flux confirm the increased energy demand of the vasoplegic state. What is novel here is that we show a fall in PCr/ATP ratio: as ATP concentrations in the cell are strictly maintained, this suggests phosphocreatine pool depletion occurs when preload is lost and cardiac output is maintained by an increase in inotropy and chronotropy. Progressive energetic depletion during high demand may give rise to contractile dysfunction over time as the heart is unable to keep up with increased requirements for ATP, which could be a mechanism of cardiac dysfunction during vasoplegia. We hypothesize this could be a contributing factor explaining cardiac dysfunction in sepsis and other conditions of distributive shock. Conflict of Interest: None